Foaming organic silicon pressure-sensitive adhesive and preparation method thereof
By using vinyl and hydrogen-containing silicone pressure-sensitive adhesive to form a sponge structure in the OLED screen pressure-sensitive adhesive, the foamed silicone pressure-sensitive adhesive with vinyl and hydrogen-containing silicone oil, the complex assembly and impact resistance in the prior art are solved. The problem of insufficient results enables thinner bonding and impact resistance, and is suitable for display modules of OLED screens.
Patent Information
- Application Number
- CN202411361486.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-27
- Publication Date
- 2025-01-03
- Estimated Expiration
- 2044-09-27
AI Technical Summary
The assembly process of existing pressure-sensitive adhesive films in OLED screen display modules is complicated, and the impact energy buffering effect is poor, resulting in the need to increase the film thickness to meet the impact resistance requirements, but this is contrary to the trend of thinning the overall thickness of the OLED screen. Moreover, the prior art sacrifices the bonding strength when improving impact resistance, and cannot effectively reduce the film thickness.
The silicon hydrogen bond addition reaction of vinyl and hydrogen-containing silicone oil is used to form a dense cross-linked mesh structure, and a hydroxy nano reinforcement agent is added to generate hydrogen to form micro bubbles, enlarge the mesh cavity to improve impact resistance, and at the same time, Nano-reinforcement agent improves mechanical strength and reduces the influence of cohesive strength, and prepares foamed silicone pressure-sensitive adhesive with sponge structure.
It achieves stronger bonding performance to glass and steel plates and stronger impact resistance at the same thickness, reduces the thickness of the film used in the display module, and maintains good cushioning performance to avoid impact of OLED screens. severe deformation and damage during the period.
Smart Images

Figure CN119242257A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of organic materials, and in particular relates to a foamed organic silicon pressure-sensitive adhesive and a preparation method thereof. Background Art
[0002] In recent years, screen display technology has developed rapidly, and the upgrade of display technology has also prompted the technological innovation of screen-related auxiliary materials. Among them, OLED screens are developing in the direction of lightweight and bendable, and the performance requirements for the pressure-sensitive adhesive film used in the display module are more stringent. At present, the mainstream pressure-sensitive adhesive film in China is acrylic foam double-sided tape. Its disadvantages are complicated assembly process and poor impact energy buffering effect. The thickness of the film needs to be increased to meet the use requirements, which is contrary to the development trend of thinning the overall thickness of OLED screens. Under the same thickness conditions, the buffering performance of silicone materials is stronger and can effectively reduce the thickness of the display module.
[0003] CN117757266A discloses a silicone gel composition, silicone gel and its application. The invention achieves both improvement of indentation and improvement of buffering effect of silicone gel by adding a controlled amount of high-pigment carbon black and modified multi-walled carbon nanotubes, and also gives silicone gel good electrical conductivity. Since its buffering performance depends on the high-density network structure of the silicone gel itself, it still needs to reach 130 microns or more to meet the impact resistance of OLED screens in order to achieve a good buffering effect.
[0004] In order to make the colloid have better impact resistance, some existing technologies sacrifice the strength of the colloid, resulting in insufficient bonding performance to glass and steel plates. At the same time, since the pressure-sensitive adhesive used in the OLED screen display module has a lower limit requirement for bonding performance, the existing technology can no longer further increase the impact resistance by reducing the bonding strength, ultimately making it impossible to reduce the thickness of the pressure-sensitive adhesive layer used in the OLED screen display module.
[0005] Therefore, in order to solve the defects of the prior art, the present invention proposes a foamed silicone pressure-sensitive adhesive, which has stronger bonding performance to glass and steel plates and stronger impact resistance at the same thickness. Summary of the invention
[0006] In order to solve the above-mentioned deficiencies in the art, an adhesive that meets the current packaging requirements of OLED screens has been invented, which can not only reduce the thickness in use but also provide bonding strength and impact resistance.
[0007] To achieve the above purpose, the technical solution adopted by the present invention is as follows:
[0008] The present invention provides a foamed organic silicon pressure-sensitive adhesive, wherein a dense cross-linked network structure is formed by addition reaction between vinyl and silicon-hydrogen bonds of hydrogen-containing silicone oil, and a hydroxy nano-reinforcer is added to react with silicon-hydrogen bonds to generate hydrogen, so that microbubbles are formed in the network structure, and the cavities in the network structure are enlarged to provide impact resistance. At the same time, the nano-reinforcer has high mechanical strength and can make up for the reduced cohesive strength caused by the cavities caused by hydrogen. The components thereof include, by weight:
[0009]
[0010] The vinyl raw rubber is one or more of vinyl-terminated polydimethylsiloxane, vinyl polydimethylsiloxane, and vinyl-terminated polymethylvinylsiloxane, and has a molecular weight of 500,000 to 800,000 and a vinyl content of 0.01 to 0.09 wt%;
[0011] The hydroxy nano reinforcing agent is one or more of nano cellulose, hydroxy carbon nanotubes, and silanol silica;
[0012] The hydroxy silicone oil is terminal hydroxymethyl polysiloxane with a viscosity of 10 to 100 mPa·s; the hydroxyl content of the terminal hydroxymethyl polysiloxane is 1 to 15%.
[0013] As a preferred technical solution of the present invention, the diameter of the nanocellulose is 3 to 5 nm, and the fiber length is 500 to 1000 nm.
[0014] As a preferred technical solution of the present invention, the M / Q value of the methyl MQ resin is 0.6-0.9, the relative molecular mass is 3500-6000 g / mol, and the hydroxyl content is less than 0.5 wt%.
[0015] As a preferred technical solution of the present invention, the M / Q value of the hydroxy MQ resin is 0.5-0.9, the relative molecular mass is 3000-6500 g / mol, and the hydroxyl content is 0.5-2.5 wt%.
[0016] As a preferred technical solution of the present invention, the inhibitor is one or more of ethynyl cyclohexanol, diallyl maleate, 2-methyl-3-butyn-2-ol, tetramethyldivinyldisiloxane, tetramethyltetravinylcyclotetrasiloxane, and 3-methyl-1-dodecyne-3-ol.
[0017] As a preferred technical solution of the present invention, the hydrogen-containing silicone oil is one or more hydrogen-containing silicone oils containing terminal hydrogen groups and pendant hydrogen groups, with a viscosity of 5-100 mPa·s and a total hydrogen content of 0.1-2.0%.
[0018] As a preferred technical solution of the present invention, the catalyst is a platinum catalyst with a platinum content of 0.25-0.6%.
[0019] As a preferred technical solution of the present invention, the organic solvent is one or more of toluene, xylene, ethyl acetate, butyl acetate, cyclohexane, n-hexane, and alkane fractions.
[0020] On the other hand, the present invention provides a method for preparing the foamed silicone pressure-sensitive adhesive:
[0021] (1) by weight, 30 to 70 parts of vinyl rubber, 5 to 10 parts of hydroxy nano reinforcing agent, 15 to 30 parts of hydroxy silicone oil, 15 to 85 parts of methyl MQ resin, 15 to 40 parts of hydroxy MQ resin, 0.01 to 0.5 parts of inhibitor, and an appropriate amount of solvent are mixed and heated to react to obtain a silicone pressure-sensitive adhesive main agent;
[0022] (2) adding an appropriate amount of solvent to the organic silicone pressure-sensitive adhesive main agent obtained in step (1) and stirring thoroughly, then adding 0.2 to 2 parts of hydrogen-containing silicone oil and stirring thoroughly, adding an appropriate amount of catalyst and stirring thoroughly, to obtain an organic silicone pressure-sensitive adhesive coating liquid;
[0023] (3) The silicone pressure-sensitive adhesive coating liquid is coated on a 50 μm thick first fluorocarbon release film, which is placed in an oven for curing and taken out. The thickness of the dry adhesive is 100 μm. A 50 μm thick second fluorocarbon release film is attached to the upper surface of the dry adhesive to obtain the foamed silicone pressure-sensitive adhesive.
[0024] As a preferred technical solution of the present invention, the solvent is one or more of anhydrous ethanol, xylene, and chloroform.
[0025] As a preferred technical solution of the present invention, the heating reaction temperature in step (1) is 120°C; the curing method in step (3) is to place the first fluorochemical release film coated with the silicone pressure-sensitive adhesive coating liquid in an oven at 100°C for curing for 1 minute, and then place it in an oven at 150°C for curing for 2 minutes before taking it out.
[0026] By adopting the above technical solution, the beneficial effects of the present invention are:
[0027] The present invention forms a dense cross-linked network structure by addition reaction between vinyl and silicon-hydrogen bonds of hydrogen-containing silicone oil, adds a hydroxyl nano-reinforcer, reacts with the silicon-hydrogen bonds to generate hydrogen, forms microbubbles filled with hydrogen in the network structure, and thus forms a dense cross-linked structure similar to a sponge. The structure has good impact resistance, and because the nano-reinforcer has high mechanical strength, it can make up for the further reduction of the cohesive strength caused by the cavity caused by hydrogen. Therefore, compared with the prior art, the present invention can effectively reduce the film thickness of the pressure-sensitive adhesive for the display module, and still meet the buffering performance requirements of the prior art.
[0028] The foamed silicone pressure-sensitive adhesive of the present invention provides good buffering performance by virtue of its microporous structure and cross-linked network structure. When the OLED screen is subjected to impact force, the cavities of the microporous structure and the cross-linked network structure will be deformed, thereby dispersing the impact force and preventing the OLED screen from being severely deformed and damaged. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] The accompanying drawings in the specification, which constitute a part of the present invention, are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute improper limitations on the present invention.
[0030] Figure 1 This is a schematic diagram of the structure of the organic silicone pressure-sensitive adhesive prepared in Example 1, Example 2, Example 3, and Example 4 of the present invention.
[0031] In the figure: 1. Silicone pressure-sensitive adhesive coating liquid; 2. First fluorochemical release film; 3. Second fluorochemical release film. DETAILED DESCRIPTION
[0032] It should be noted that the following detailed descriptions are all illustrative and intended to provide further explanation of the present invention. Unless otherwise specified, all technical and scientific terms used herein have the same meanings as those commonly understood by those skilled in the art to which the present invention belongs.
[0033] It should be noted that the terms used herein are only for describing specific embodiments and are not intended to limit exemplary embodiments according to the present invention. As used herein, unless the context clearly indicates otherwise, the singular form is also intended to include the plural form. In addition, it should be understood that when the terms "comprise" and / or "include" are used in this specification, it indicates the presence of features, steps, operations, devices, components and / or combinations thereof.
[0034] The present invention will be further explained below in conjunction with the accompanying drawings and embodiments.
[0035] Example 1
[0036] Ingredients include:
[0037] First Vinyl Rubber 35g
[0038] Second Vinyl Rubber 5g
[0039] Hydroxy silicone oil 15g
[0040] Xylene 150g
[0041] Hydroxyl nano reinforcing agent 5g
[0042] Methyl MQ resin 40g
[0043] Hydroxy MQ resin 12g
[0044] Inhibitor 0.01g
[0045] 0.3g hydrogen silicone oil;
[0046] Catalyst 0.8g.
[0047] in,
[0048] The first vinyl raw rubber is methyl vinyl polysiloxane: weight average molecular weight 650,000, vinyl content 0.06wt%;
[0049] The second vinyl raw rubber is methyl vinyl polysiloxane with a weight average molecular weight of 800,000 and a vinyl content of 0.09wt%;
[0050] The nano reinforcing agent is nano cellulose: the fiber diameter is 3-5 nm, and the fiber length is 500-1000 nm;.
[0051] The methyl MQ resin has an M / Q ratio of 0.75, a molar mass of 5000 g / mol, and a hydroxyl content of 0.3 wt %.
[0052] The hydroxy MQ resin has an M / Q ratio of 0.75, a molar mass of 3000 g / mol, and a hydroxyl content of 3.0 wt%.
[0053] The inhibitor is ethynyl cyclohexanol.
[0054] The hydrogen-containing silicone oil is a hydrogen-containing silicone oil with a pendant hydrogen group: the viscosity is 9 mPa.s and the hydrogen content is 1.6%.
[0055] The catalyst is a platinum catalyst: the platinum content is 5000ppm.
[0056] 35g of the first vinyl rubber, 5g of the second vinyl rubber, 15g of hydroxy silicone oil, 5g of nanocellulose, 40g of methyl MQ resin, 5g of hydroxy MQ resin, 0.01g of inhibitor, and 80g of xylene were added to a three-necked flask, stirred at 120°C for 4 hours, and refluxed twice to obtain a silicone pressure-sensitive adhesive main agent; 70g of xylene was added to the silicone pressure-sensitive adhesive main agent, stirred with an electric stirrer for 5 minutes, then 0.3g of hydrogenated silicone oil was added dropwise, stirred with an electric stirrer for 5 minutes, and finally 0.8g of catalyst was added dropwise, stirred with an electric stirrer for 5 minutes to obtain a silicone pressure-sensitive adhesive coating liquid. The silicone pressure-sensitive adhesive coating liquid was applied on a 50μm thick first fluorine release film, placed in an oven at 100°C for curing for 1min, and then placed in an oven at 150°C for curing for 2min and then taken out, the dry adhesive thickness was 100μm, and a 50μm thick second fluorine release film was attached. A foamed silicone pressure-sensitive adhesive sample film was prepared.
[0057] Example 2
[0058] Ingredients include:
[0059] First Vinyl Rubber 35g
[0060] Second Vinyl Rubber 5g
[0061] Hydroxy silicone oil 20g
[0062] Xylene 150g
[0063] Hydroxyl nano reinforcing agent 5g
[0064] Methyl MQ resin 40g
[0065] Hydroxy MQ resin 12g
[0066] Inhibitor 0.01g
[0067] The first hydrogen-containing silicone oil 0.3g;
[0068] The second hydrogen-containing silicone oil 0.3g;
[0069] Catalyst 0.8g.
[0070] in,
[0071] The first vinyl raw rubber is methyl vinyl polysiloxane: weight average molecular weight 650,000, vinyl content 0.06wt%;
[0072] The second vinyl raw rubber is methyl vinyl polysiloxane with a weight average molecular weight of 800,000 and a vinyl content of 0.09wt%;
[0073] The nano reinforcing agent is nano cellulose: the fiber diameter is 3-5 nm, and the fiber length is 500-1000 nm;.
[0074] The methyl MQ resin has an M / Q ratio of 0.75, a molar mass of 5000 g / mol, and a hydroxyl content of 0.3 wt %.
[0075] The hydroxy MQ resin has an M / Q ratio of 0.75, a molar mass of 3000 g / mol, and a hydroxyl content of 3.0 wt%.
[0076] The inhibitor is ethynyl cyclohexanol.
[0077] The first hydrogen-containing silicone oil is a hydrogen-containing silicone oil with pendant hydrogen groups: viscosity 9 mPa.s, hydrogen content 1.4%.
[0078] The second hydrogen-containing silicone oil is a hydrogen-terminated hydrogen-containing silicone oil with a viscosity of 15 mPa.s and a hydrogen content of 0.2%.
[0079] The catalyst is a platinum catalyst: the platinum content is 5000ppm.
[0080] The preparation method is the same as that in Example 1.
[0081] Example 3
[0082] Ingredients include:
[0083] Vinyl rubber 40g
[0084] Hydroxy silicone oil 30g
[0085] Xylene 150g
[0086] Nano reinforcing agent 8g
[0087] Methyl MQ resin 44g
[0088] Hydroxy MQ resin 8g
[0089] Inhibitor 0.01g
[0090] 0.3g hydrogen silicone oil;
[0091] Catalyst 0.8g.
[0092] in,
[0093] The vinyl raw rubber is methyl vinyl polysiloxane: weight average molecular weight 650,000, vinyl content 0.06wt%;
[0094] The nano reinforcing agent is nano cellulose: the fiber diameter is 3-5 nm, and the fiber length is 500-1000 nm;.
[0095] The methyl MQ resin has an M / Q ratio of 0.75, a molar mass of 5000 g / mol, and a hydroxyl content of 0.3 wt %.
[0096] The hydroxy MQ resin has an M / Q ratio of 0.75, a molar mass of 3000 g / mol, and a hydroxyl content of 3.0 wt%.
[0097] The inhibitor is ethynyl cyclohexanol.
[0098] The hydrogen-containing silicone oil is a hydrogen-containing silicone oil with a pendant hydrogen group: the viscosity is 9 mPa.s and the hydrogen content is 1.6%.
[0099] The catalyst is a platinum catalyst: the platinum content is 5000ppm.
[0100] The preparation method is the same as that in Example 1.
[0101] Example 4
[0102] Ingredients include:
[0103] Vinyl rubber 40g
[0104] Hydroxy silicone oil 25g
[0105] Xylene 150g
[0106] Nano reinforcing agent 8g
[0107] Methyl MQ resin 44g
[0108] Hydroxy MQ resin 8g
[0109] Inhibitor 0.01g
[0110] 0.3g hydrogen silicone oil;
[0111] Catalyst 0.8g.
[0112] in,
[0113] The vinyl raw rubber is methyl vinyl polysiloxane: weight average molecular weight 650,000, vinyl content 0.06wt%;
[0114] The nano reinforcing agent is a mixture of silanol silicon dioxide and nano cellulose in a mass ratio of 1:1.
[0115] The methyl MQ resin has an M / Q ratio of 0.75, a molar mass of 5000 g / mol, and a hydroxyl content of 0.3 wt %.
[0116] The hydroxy MQ resin has an M / Q ratio of 0.75, a molar mass of 3000 g / mol, and a hydroxyl content of 3.0 wt%.
[0117] The inhibitor is ethynyl cyclohexanol.
[0118] The hydrogen-containing silicone oil is a hydrogen-containing silicone oil with a pendant hydrogen group: the viscosity is 9 mPa.s and the hydrogen content is 1.6%.
[0119] The catalyst is a platinum catalyst: the platinum content is 5000ppm.
[0120] The preparation method is the same as that in Example 1.
[0121] In order to verify the technical effect of the present invention, a comparative test was conducted to form the following comparative examples using the preparation of common adhesives in the prior art.
[0122] Comparative Example 1
[0123] Ingredients include:
[0124] Vinyl rubber 51g
[0125] Methyl MQ resin 74g
[0126] Xylene 150g
[0127] Inhibitor 0.01g
[0128] The first hydrogen-containing silicone oil 0.15g
[0129] The second hydrogen-containing silicone oil 0.15g
[0130] Catalyst 0.8g
[0131] in,
[0132] The vinyl raw rubber is methyl vinyl polysiloxane: weight average molecular weight 650,000, vinyl content 0.06wt%;
[0133] The methyl MQ resin has an M / Q ratio of 0.75, a molar mass of 5000 g / mol, and a hydroxyl content of 0.3 wt %.
[0134] The inhibitor is ethynyl cyclohexanol.
[0135] The first hydrogen-containing silicone oil is a hydrogen-containing silicone oil with pendant hydrogen groups: viscosity 9 mPa.s, hydrogen content 1.4%.
[0136] The second hydrogen-containing silicone oil is a hydrogen-terminated hydrogen-containing silicone oil with a viscosity of 15 mPa.s and a hydrogen content of 0.2%.
[0137] The catalyst is a platinum catalyst: the platinum content is 5000ppm.
[0138] Preparation method
[0139] Take 51g of vinyl raw rubber, 74g of methyl MQ resin, and 0.01g of inhibitor, add 150g of xylene, stir with an electric stirrer for 5 minutes, then drop 0.15g of the first hydrogen-containing silicone oil, stir with an electric stirrer for 5 minutes, then drop 0.15g of the second hydrogen-containing silicone oil, stir with an electric stirrer for 5 minutes, and finally drop 0.8g of catalyst, stir with an electric stirrer for 5 minutes to obtain a silicone pressure-sensitive adhesive coating liquid. The silicone pressure-sensitive adhesive coating liquid is applied on a 50μm thick first fluorine release film, placed in an oven at 100°C for 1min to cure, then placed in an oven at 150°C for 2min to cure, and then taken out. The dry adhesive thickness is 100μm, and a 50μm thick second fluorine release film is attached. A foamed silicone pressure-sensitive adhesive sample film is obtained.
[0140] Comparative Example 2
[0141] Ingredients include:
[0142] First Vinyl Rubber 35g
[0143] Second Vinyl Rubber 25g
[0144] Xylene 150g
[0145] Methyl MQ resin 40g
[0146] Hydroxy MQ resin 12g
[0147] Inhibitor 0.01g
[0148] 0.3g hydrogen silicone oil;
[0149] Catalyst 0.8g.
[0150] in,
[0151] The first vinyl raw rubber is methyl vinyl polysiloxane: weight average molecular weight 650,000, vinyl content 0.06wt%;
[0152] The second vinyl raw rubber is methyl vinyl polysiloxane with a weight average molecular weight of 800,000 and a vinyl content of 0.09wt%;
[0153] The methyl MQ resin has an M / Q ratio of 0.75, a molar mass of 5000 g / mol, and a hydroxyl content of 0.3 wt %.
[0154] The hydroxy MQ resin has an M / Q ratio of 0.75, a molar mass of 3000 g / mol, and a hydroxyl content of 3.0 wt%.
[0155] The inhibitor is ethynyl cyclohexanol.
[0156] The hydrogen-containing silicone oil is a hydrogen-containing silicone oil with a pendant hydrogen group: the viscosity is 9 mPa.s and the hydrogen content is 1.4%.
[0157] The catalyst is a platinum catalyst: the platinum content is 5000ppm.
[0158] Preparation method:
[0159] Take 35g of the first vinyl rubber, 25g of the second vinyl rubber, 40g of methyl MQ resin, 12g of hydroxyl MQ resin, and 0.01g of the inhibitor, add 150g of xylene, stir with an electric stirrer for 5 minutes, then drop 0.3g of hydrogenated silicone oil, stir with an electric stirrer for 5 minutes, and finally drop 0.8g of catalyst, stir with an electric stirrer for 5 minutes to obtain a silicone pressure-sensitive adhesive coating liquid. The silicone pressure-sensitive adhesive coating liquid is applied on a 50μm thick first fluorine release film, placed in an oven at 100°C for 1min, and then placed in an oven at 150°C for 2min before curing. The dry adhesive thickness is 100μm, and a 50μm thick second fluorine release film is attached. A foamed silicone pressure-sensitive adhesive sample film is obtained and tested.
[0160] Comparative Example 3
[0161] Ingredients include:
[0162]
[0163] Preparation method:
[0164] 35g of vinyl rubber, 30g of hydroxy silicone oil, 35g of methyl MQ resin, 0.01g of inhibitor, and 66g of xylene were added to a three-necked flask, stirred at 120°C for 4 hours, and refluxed twice to obtain a silicone pressure-sensitive adhesive main agent; 30g of silicone pressure-sensitive adhesive main agent was taken, 15g of xylene was added, and stirred with an electric stirrer for 5 minutes, then 0.09g of hydrogenated silicone oil was added dropwise, and stirred with an electric stirrer for 5 minutes, and finally 0.24g of catalyst was added dropwise, and stirred with an electric stirrer for 5 minutes to obtain a silicone pressure-sensitive adhesive coating liquid. The silicone pressure-sensitive adhesive coating liquid was applied on a 50μm thick first fluorine release film, placed in an oven at 100°C for curing for 1min, and then placed in an oven at 150°C for curing for 2min and then taken out, the dry glue thickness was 100μm, and a 50μm thick second fluorine release film was attached. A foamed silicone pressure-sensitive adhesive sample film was obtained.
[0165] The samples prepared in the above-mentioned embodiments and comparative examples were tested, and the testing method included:
[0166] (1) 180° peel strength test: According to GB / T 2792-2014 "Test method for peel strength of adhesive tape", the sample is cut into 25 mm wide strips, the second fluorine release film is torn off and the 25μ PET original film is attached. The other side is attached to the SUS standard test plate to test the 180° peel strength of the tape;
[0167] (2) 85℃ high temperature 180° peel strength immediate test: According to GB / T 2792~2014 "Test method for peel strength of adhesive tape", cut the sample strip to 25mm width, tear off the second fluorine release film and stick the 25μPET original film, stick the other side to the SUS standard test plate and place it in an 85℃ oven for 5 minutes, then immediately test the 180° peel strength;
[0168] (3) Point impact resistance: Tear off the first fluorine release film and the second fluorine release film from the sample mold, and fix it on the base of the device, which has a force sensor. Place a steel ball of a certain size at a height of 150 mm, and use a solenoid valve to control the steel ball to drop vertically. Record the force value F1 of the steel ball falling on the sample film, take out the sample film, and repeat the ball drop test. Record the force value F0 of the steel ball falling directly on the base. The point impact rate is (F0-F1) / F0, and the point impact resistance is required to be greater than 65%.
[0169] Test results: (100μm adhesive thickness)
[0170] Test specimen 180° peel force (gf / inch) 85℃ high temperature 180° peeling force (gf / inch) Point impact resistance (%) Example 1 1729 720 72 Example 2 1663 612 74 Example 3 1889 721 68 Example 4 1796 572 65 Comparative Example 1 1157 353 58 Comparative Example 2 1260 460 66 Comparative Example 3 420 125 69
[0171] It can be seen that the peel strength of Example 1 and Example 3 belong to the first echelon, but the point impact resistance rate of Example 3 is not as good as that of Example 1. Overall, the technical performance of Example 1 is the best. In Example 2, due to the selection of compound hydrogen-containing silicone oil, the addition of terminal hydrogen-containing silicone oil, and the increase of the length of the silicon-hydrogen cross-linked chain segment, the colloid modulus is lower and has a higher point impact resistance rate, but the strength is reduced, resulting in a decrease in bonding strength. Example 3 increases the amount of low molecular weight vinyl raw rubber, methyl MQ resin and hydroxyl nano-reinforcement agent added. Example 3 has higher colloid cohesive strength than Example 1, but the number of microbubbles is reduced and the point impact resistance rate is reduced. Example 4 adopts the scheme of compound nano-reinforcement agent compared with Example 3. Example 4 is more resistant to high temperature than Example 3, but the bonding strength and point impact resistance rate are reduced.
[0172] In Comparative Example 1, since no hydroxyl nano-reinforcer is added, the colloidal modulus is lower by only adding terminal hydrogen-containing silicone oil. However, since its bonding strength is greatly reduced, the point impact resistance rate is also the lowest among all experimental examples.
[0173] Comparative Example 2 improves the cohesive strength by compounding vinyl rubber and MQ resin, and the bonding strength and point impact resistance rate are improved compared with Comparative Example 1, but there is still a large gap compared with the embodiment. Comparative Example 3 uses hydroxy silicone oil for foaming, and does not add hydroxy nano reinforcing agent. It can be seen that Comparative Example 3 has a better point impact resistance rate than the embodiment, but the bonding strength is lower.
[0174] Finally, it can be seen that the foamed silicone pressure-sensitive adhesive of the present invention has the performance of both bonding strength and point impact resistance.
[0175] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A foamed silicone pressure-sensitive adhesive, characterized in that: Through the addition reaction of vinyl and the silicon-hydrogen bond of hydrogen-containing silicone oil, a dense cross-linked network structure is formed, and a hydroxyl nano-reinforcer is added to react with the silicon-hydrogen bond to generate hydrogen, so that microbubbles are formed in the network structure, and the cavities in the network structure are enlarged to provide impact resistance. At the same time, the nano-reinforcer has a high mechanical strength and can make up for the reduced cohesive strength caused by the cavity caused by hydrogen. The components include by weight: The vinyl raw rubber is one or more of vinyl-terminated polydimethylsiloxane, vinyl polydimethylsiloxane, and vinyl-terminated polymethylvinylsiloxane, and has a molecular weight of 500,000 to 800,000 and a vinyl content of 0.01 to 0.09 wt%; The hydroxy nano reinforcing agent is one or more of nano cellulose, hydroxy carbon nanotubes, and silanol-silicon dioxide; The hydroxy silicone oil is terminal hydroxymethyl polysiloxane with a viscosity of 10 to 100 mPa·s; the hydroxy content of the terminal hydroxymethyl polysiloxane is 1 to 15%.
2. The pressure-sensitive adhesive according to claim 1, characterized in that: The diameter of the nanocellulose is 3-5 nm, and the fiber length is 500-1000 nm.
3. The pressure-sensitive adhesive according to claim 1, characterized in that: The M / Q value of the methyl MQ resin is 0.6-0.9, the relative molecular mass is 3500-6000 g / mol, and the hydroxyl content is less than 0.5 wt%.
4. The pressure-sensitive adhesive according to claim 1, characterized in that: The hydroxy MQ resin has an M / Q value of 0.5 to 0.9, a relative molecular mass of 3000 to 6500 g / mol, and a hydroxyl content of 0.5 to 2.5 wt %.
5. The pressure-sensitive adhesive according to claim 1, characterized in that: The inhibitor is one or more of ethynyl cyclohexanol, diallyl maleate, 2-methyl-3-butyn-2-ol, tetramethyldivinyldisiloxane, tetramethyltetravinylcyclotetrasiloxane, and 3-methyl-1-dodecyn-3-ol.
6. The pressure-sensitive adhesive according to claim 1, characterized in that: The hydrogen-containing silicone oil is one or more hydrogen-containing silicone oils containing terminal hydrogen groups and side hydrogen groups, with a viscosity of 5 to 100 mPa·s and a total hydrogen content of 0.1 to 2.0%.
7. The pressure-sensitive adhesive according to claim 1, characterized in that: The catalyst is a platinum catalyst, and the platinum content is 0.25-0.6%.
8. The pressure-sensitive adhesive according to claim 1, characterized in that: The organic solvent is one or more of toluene, xylene, ethyl acetate, butyl acetate, cyclohexane, n-hexane, and alkane fractions.
9. A method for preparing a foamed silicone pressure-sensitive adhesive according to any one of claims 1 to 7, characterized in that: The preparation method is: (1) by weight, 30 to 70 parts of vinyl rubber, 5 to 10 parts of hydroxy nano reinforcing agent, 15 to 30 parts of hydroxy silicone oil, 15 to 85 parts of methyl MQ resin, 15 to 40 parts of hydroxy MQ resin, 0.01 to 0.5 parts of inhibitor, and 100 to 200 parts of organic solvent are mixed and heated for reaction to obtain a main agent of organic silicone pressure-sensitive adhesive; (2) adding an appropriate amount of organic solvent to the organic silicone pressure-sensitive adhesive main agent obtained in step (1) and stirring thoroughly, then adding 0.2-2 parts of hydrogenated silicone oil and stirring thoroughly, and adding 0.3-2 parts of a catalyst and stirring thoroughly to obtain an organic silicone pressure-sensitive adhesive coating liquid; (3) The silicone pressure-sensitive adhesive coating liquid is coated on a 50 μm thick first fluorocarbon release film, which is placed in an oven for curing and taken out. The thickness of the dry adhesive is 100 μm. A 50 μm thick second fluorocarbon release film is attached to the upper surface of the dry adhesive to obtain the foamed silicone pressure-sensitive adhesive.
Citation Information
Patent Citations
Addition type curable polysiloxane packaging silica gel composition as well as preparation method and application thereof
CN112680176A
Heat-conducting adhesive for power battery and preparation method thereof
CN112708395A
Organic silicon pouring sealant with high thermal conductivity and high strength and preparation method thereof
CN116554834A
Low-density foamed silica gel and preparation method thereof
CN116640550A
Foamable Silicone Composition, Preparation Method and Use Thereof
US20220169814A1
Cited By
High-hardness foamed silicone rubber and preparation method thereof
CN119570264A
Preparation method and application of photocuring sulfydryl silicon resin and organic silicon pressure-sensitive adhesive
CN120059193A